Chimeric Antigen Receptor (CAR)-T Cell Immunotherapy Against Thoracic Malignancies: Challenges and Opportunities - Long Chen; Fukun Chen; Huatao Niu; Jindan Li; Yongzhu Pu; Conghui Yang; Yue Wang; Rong Huang; Ke Li; Yujie Lei; Yunchao Huang (Frontiers in Immunology, 2022)
Different from surgery, chemical therapy, radio-therapy and target therapy, Chimeric antigen receptor-modified T (CAR-T) cells, a novel adoptive immunotherapy strategy, have been used successfully against both hematological tumors and solid tumors. Although several problems have reduced engineered CAR-T cell therapeutic outcomes in clinical trials for the treatment of thoracic malignancies, including the lack of specific antigens, an immunosuppressive tumor microenvironment, a low level of CAR-T cell infiltration into tumor tissues, off-target toxicity, and other safety issues, CAR-T cell treatment is still full of bright future. In this review, we outline the basic structure and characteristics of CAR-T cells among different period, summarize the common tumor-associated antigens in clinical trials of CAR-T cell therapy for thoracic malignancies, and point out the current challenges and new strategies, aiming to provide new ideas and approaches for preclinical experiments and clinical trials of CAR-T cell therapy for thoracic malignancies.